Lived experiences of mothers having children with autism in kathmandu. - Ghimire, Rachana (2012)
ABSTRACT: Autism is neuro developmental disorder, starts at first three years of life and more common in boys than girls has no definite cause and treatment. This condition is life-long so needs life-long support and guide. Rearing and managing child with autism is a challenging task so mothers need support and help. This qualitative study was conducted with the objective of exploring the lived experience of mothers who were taking care of children with autism; in Autism Care Nepal, Gairidhara Kathmandu by using a phenomenological method, 10 mothers having children with autism were selected. Data was gathered by using in-depth interview guideline. Respondent's verbal as well as nonverbal clues were recorded by observation. Three to five in-depth interviews were carried out with each respondent along with audio tape recording and field notes. Supplementary data were collected by observing the children's behavior and activities in day care center to give light to the findings of this study. Collected information was first transcribed from the verbatim then translated into English for reporting. The voluminous information was reduced to smaller statements to get the actual meanings which were coded, categorized and organized into 10 clusters of themes: behavior of the children, mode of treatment, reaction to diagnosis, experiences of therapeutic process, management of activities of daily living, cost management, social life, burden/satisfaction, experiences regarding schooling of the children and coping mechanisms. Again the respondents were reconfirmed for the given information by making revisits. Findings revealed that mother's age ranged from 28 to 40 years. All were literate; belonged to middle class family and from Kathmandu Valley. Regarding occupation of the respondents, five out of ten were service holder; three out of five had engaged in Autism Care Nepal in different areas after their children were diagnosed as autism. The interpretations of the themes which are substantiated with the evidence of verbatim of in-depth interview revealed that all children demonstrated change in their behavior, like- shouting/crying, rolling on the ground, beating and pinching other people without obvious reasons in any place like hospital, public bus or public gathering that made the mother even difficult to manage and control the child. All of the mothers were shocked after they heard about autism for the first time. All of the mothers realized that there was difficult to maintain active social relation as before. The most painful experiences of mothers (8 out of 10) were the schooling of the child. These study findings present individual differences in application of measures to relieve worries, all of the respondents had reported that uncontrollable behaviors of their children caused emotional breakdown, sometimes crying too. They used to relieve their worries by sharing experiences with other mothers with similar problems. Based on identified concepts, it is recommended that public awareness programme throughout the country should be conducted. In this study all of the respondents have experiences that the general population has little or no knowledge about autism, some of them also experiences that in many health institutions and school; the health personnel and teachers also exhibited lack of knowledge on autism.